Validation of a Tool to Measure the Digital Competence of Students from Universidad Latina - Chavarria , Aleida; Santiago, Raúl; Palau, Ramon; Quiroz, Juan Silva (Journal of Ecohumanism, 2025)
Digital competence (DC) is essential in higher education, supporting academic, professional, and cultural development. This study aimed to validate the COMPDIG-PED instrument for assessing digital competence among students at Universidad Latina. Data were collected using non-probabilistic convenience sampling during the second quarter of 2024. Reliability analysis revealed satisfactory internal consistency, with Cronbach´s alpha (α = .70). However, the distribution of item difficulty highlighted a significant imbalance, as 36.51% of items were classified as very difficult, while only 12.70% fell into the medium-difficulty range. Participants scored between 12 and 41 (M = 31.52, SD = 5.05) out of a maximum of 63 points. These results highlighted the need to recalibrate item difficulty to enhance the instrument´s diagnostic value. Confirmatory factor analysis further raised concerns regarding the instrument´s unidimensionality. The Kaiser-Meyer-Olkin (KMO) value was low (2.0), and Bartlett´s test was significant (p< .001), indicating weak inter-item correlations. Additionally, low alpha values (0.13 – 0.55) within specific factors suggested issues with item alignment and clarity. These findings emphasize the need for refinements to the COMPDIG-PEG instrument to improve its design, structure, and reliability, ensuring it provides a comprehensive assessment of digital competences in higher education contexts.